Lung Tumor Microenvironment Induces Specific Gene Expression Signature in Intratumoral NK Cells - Gillard-Bocquet, Mélanie; Caer, Charles; Cagnard, Nicolas; Crozet, Lucile; Perez, Mikael; Fridman, Wolf Hervé; Sautes-fridman, Catherine; Cremer, Isabelle (Frontiers in Immunology, 2013)
Natural Killer (NK) cells are able to recognize and kill tumor cells, however whether they contribute to tumor immunosurveillance is still debated. Our previous studies demonstrated the presence of NK cells in human lung tumors. Their comparison with NK cells from non-tumoral lung tissues and with blood NK cells from the same individuals revealed a decreased expression of some NK receptors and impaired ex vivo cytotoxic functions occurring specifically in NK cells isolated from the tumor microenvironment. The aim of the present study was to characterize the transcriptional profile of such intratumoral NK cells, by comparative microarray analysis of sorted NK cells isolated from non tumoral (NonTum-NK) and tumoral (Tum-NK) lung tissues of twelve Non-Small Cell Lung Cancer (NSCLC) patients. Our results reveal a specific gene expression signature of Tum-NK cells particularly in activation processes and cytotoxicity, confirming that tumor environment induces modifications in NK cells biology. Indeed, intratumoral NK cells display higher expression levels of NKp44, NKG2A, Granzyme A and K and Fas mRNA. A particular pattern of receptors involved in chemotaxis was also observed, with an overexpression of CXCR5 and CXCR6, and a lower expression of CX3CR1 and S1PR1 genes in Tum-NK as compared to NonTum-NK cells. The precise identification of the molecular pathways modulated in the tumor environment will help to decipher the role of NK cells in tumor immunosurveillance and will open future investigations to manipulate their antitumoral functions.